2019
DOI: 10.31883/pjfns/109423
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction of Different Groups of Phenolic Compounds from Grape Skin Pomaces: Modeling and Optimization

Abstract: This means that grape pomace still exhibits high levels of bioactive compounds (60-70%) with strong antioxidant, antibacterial, and cytotoxic activities as well as favorable pharmacological properties [Bartolomé et al., 2004; Peixoto et al., 2018]. These compounds are known to contribute to human health and are particularly associated with reduced incidence of cardiovascular diseases as atherosclerosis and hypertension, neurodegeneration, and similar medical conditions [Auger et al., 2004; De Sales et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…When comparing the results obtained with data reported in the literature for GP extracts, it is observed that ORAC values found in the pre-sent study are up to 12 times higher. In the case of MAE using methanol 60 % as a solvent, an ORAC value of 31.982,06 µg TRO-LOX/g [33] was reported, whereas for SOL, a value of 68.204,03 µg TROLOX/g was found [25]. This indicates that the operating conditions used in the extraction significantly affect the antioxidant capacity of the extracts.…”
Section: Extract Characterizationmentioning
confidence: 98%
“…When comparing the results obtained with data reported in the literature for GP extracts, it is observed that ORAC values found in the pre-sent study are up to 12 times higher. In the case of MAE using methanol 60 % as a solvent, an ORAC value of 31.982,06 µg TRO-LOX/g [33] was reported, whereas for SOL, a value of 68.204,03 µg TROLOX/g was found [25]. This indicates that the operating conditions used in the extraction significantly affect the antioxidant capacity of the extracts.…”
Section: Extract Characterizationmentioning
confidence: 98%
“…In literature, ANN based modelling has been recently applied for simulation and optimization for the extractions of phenolic compounds from garlic [18], green and black tea [19], cocoa shell [20], sweet potato peel [21], peppermint [22], grape skin pomaces [23], and to predict the particle size of phenolic compounds in nano-systems [24]. However, there have been no studies modeling and analyzing the extraction of phenolic compounds from fenugreek seeds by ANN.…”
Section: Introductionmentioning
confidence: 99%
“…New unconventional techniques have emerged that can reduce extraction time, process temperature and solvent consumption, thus contributing to higher extraction efficiency and lower energy consumption. Some of the most relevant technologies are: ultrasonic-assisted extraction (UAE) [ 6 , 34 ], microwave-assisted extraction (MAE) [ 35 , 36 ], supercritical fluid extraction (SFE) [ 37 ], liquid pressure extraction (PLE) [ 38 ], ohmic heating (OH) [ 39 ], pulsed electric fields (PEF) [ 40 , 41 ] and enzyme-assisted extraction (EAE) [ 42 ]. Some enzymes, such as cellulases, hemicellulases, pectinases or amylases, can break down or weaken cell walls, releasing cytoplasmic contents (e.g., phenolic compounds) into the extraction solvent and thus improving extraction recovery.…”
Section: Introductionmentioning
confidence: 99%